Legal Tools for Urban Regeneration - Gheduzzi, Simone (Sens public)

(untitled) (Département des littératures de langue française, 2024)
The contemporary debate, in terms of urban redevelopment, has identified common goods as its reference model, outlining a way of intervention that provides the direct participation of citizens in forms of management based on self-government, direct democracy and the absence of imposed hierarchies. In these terms, private law, overcoming urban planning and public law, can help build a civic community in which innovation processes that are not directly attributable to the power of the administrator arise. In this sense, the paper intends to investigate three legal instruments that could facilitate the implementation of these processes: The Common Good Foundation, which basically consists in deducing in the private legal form of the open foundation not only a complex of passive assets, but also a collective activity and subjectivity. The trust, which can be useful for accelerating processes, making them more competitive in terms of efficiency, transparency, and targeted use of resources from where the public cedes powers to the private sector. The SPAB (Società per Azioni Buone), a newly born instrument in Favara (Agrigento), which aims to create a company open to everyone: every citizen can be a shareholder and therefore owner of a small piece of town. Bottom-up practices that aim to give voice to citizens’ needs are the lifeblood to support and implement the various urban projects. The tools described in this paper want to stimulate this scenario of regeneration and therefore to implement a practice of redemption of public spaces by citizens.